Tracking A Dynamic Target in Wireless Sensor Network Using Enhanced Polygon Based Framework (International Journal of Engineering and Computer Science, 2014)
The Main objective of a Wireless Sensor Network is to provide reliable and accurate information regarding the environment in which the sensors are deployed. Among the various applications of a sensor network, recent advances are with respect to target tracking. Target tracking is a challenging task due to failure of sensor nodes, high mobility of the target, processing of data acquired from multiple targets and multiple sensors at sink, communication between the sensors using wireless medium. Many approaches have been developed to address the issues of target tracking and provide the solution for the same. In this paper we present the various mechanisms developed for the purpose of target tracking using the target signal parameters such as Received Signal Strength( RSS ) and Time of Arrival( ToA ). Finally we propose a target tracking framework considering the flaws in existing system and combining the advantages of various mechanism with energy of a sensor node being the main constraint.